Legal Protection for Victims of Wrongful Arrest Children Viewed from the Perspective of the Juvenile Criminal Justice System: Perlindungan Hukum Terhadap Korban Salah Tangkap Anak Ditinjau dari Perspektif Sistem Peradilan Pidana AnakLegal Protection for Victims of Wrongful Arrest Children Viewed from the Perspective of the Juvenile Criminal Justice System - Prameswari, Larasati (Annual Review of Legal Studies, 2024)
Cases of wrongful arrest in Indonesia still frequently occur due to procedural violations and incorrect identification of perpetrators which are seen as a result of weak professionalism of law enforcement officials. Cases of wrongful arrest in Indonesia not only affect the adult population but also minors. adequate compensation in accordance with applicable laws and regulations. This normative legal research uses a qualitative research approach because it discusses an event, namely the incident of wrongful arrest of a child in Indonesia, using a statutory approach and a case approach. In implementing a juvenile justice system in accordance with Law Number 11 of 2012, there are principles that can be used as a basis for implementing the enforcement of the juvenile justice system, according to which children who are in conflict with the law, whether as perpetrators, witnesses or victims, should be treated in accordance with applicable regulations. and does not violate these principles. However, the fact is that there are still many cases of wrongful arrests experienced by minors, thus making minors victims of the enforcement of the justice system itself. Errors in person that often occur in enforcing the criminal justice system result in violations of the rights of children in conflict with the law, both as perpetrators, witnesses and victims. The form of recovery and compensation that children who are victims of wrongful arrest should receive must also be adjusted to the provisions of the Child Protection Law and also the Child Criminal Justice System Law.